Avaliando o Tratamento de Exceção em um Sistema Web Corporativo: Um Estudo de Caso - Sousa , Dêmora Bruna Cunha de; Carvalho, Windson Viana de; Rocha, Lincoln Souza (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2017)
The exception handling has necessary elements for the development of a fault-tolerant Web system. Although, even with its high importance, studies indicate a neglect and low quality of the exception handling development. This research aims to conduct an in-depth analysis of exception handling, exploring human and technical relevant aspects obtained from a corporate environment Web system. We have initiated the first unit of analysis. It regards the developers’ perception of exception handling on an organisation. Among the obtained results, it is possible to realise that the importance of the exceptional flows is recognised, and developers suggest its normalisation would bring benefits to the developed systems. During the case study is intended to assess the quality of the exception handling on the target systems comparing to the developers’ background, moreover, institutionalise rules to the implemented exception handling.